2022
DOI: 10.1002/jgm.3441
|View full text |Cite
|
Sign up to set email alerts
|

SYNGR2 serves as a prognostic biomarker and correlates with immune infiltrates in esophageal squamous cell carcinoma

Abstract: Background: Synaptogyrin-2 (SYNGR2) plays an important role in regulating membrane traffic in non-neuronal cells. However, the role of SYNGR2 in esophageal squamous cell carcinoma (ESCC) remains unclear.Methods: All original data were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and integrated via R 3.5.3. SYNGR2 expression was explored in the TCGA and GEO databases. The correlations between SYNGR2 and cancer immune characteristics were analyzed via the TIMER and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have found that the expression of SYNGR2 in esophageal cancer is related to immune cell infiltration [ 7 ]. Based on this, the Estimating Relative Subsets of RNA Transcripts (CIBERSORT) algorithm was used to determine the composition of 22 immune cell subsets based on gene expression profiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found that the expression of SYNGR2 in esophageal cancer is related to immune cell infiltration [ 7 ]. Based on this, the Estimating Relative Subsets of RNA Transcripts (CIBERSORT) algorithm was used to determine the composition of 22 immune cell subsets based on gene expression profiles.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the evidence of SYNGR2’s implications in cancer is very preliminary and lacks experimental validation. Li et al [ 7 ] reported the elevated expression of SYNGR2 in ESCC. High SYNGR2 expression was associated with poorer OS in ESCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation